The genus Arhopalus Serville, 1834 (Insecta: Coleoptera: cerambycidae: Aseminae) in aáociation to Sirex noctilio in Argentina - Lopez, A.=700 1 Garcia, J.; Demaestri, M.; Di Iorio, O.; Magris, R.
(Es, En)
Ilus., 11 ref.
Keywords: PINUS ELLIOTTII; INSECTOS PERFORADORES DE LA MADERA; SIREX; ARGENTINA; AMERICA DEL SUR; ARTHOPALUS; BOLETIN DE SANIDAD VEGETAL: PLAGAS